2008
DOI: 10.1080/03602550802497776
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Novolak Resin by Liquefaction of Oil Palm Empty Fruit Bunches (EFB) and Characterization of EFB Residue

Abstract: Liquefaction of empty fruit bunches (EFB) in phenol was carried out in the presence of various types of acids as catalyst. Then the nonreacted EFB (residue) was analyzed using the X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, thermal gravimetric analysis (TGA), and scanning electron microscopy. The result show that strong acids produce lower residue compared to weak acids. The TGA results show that the residue possesses a better hydrophobicity and better heat resistance compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The study of reaction mechanisms must rely on analytical chemical methods, such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), gel permeation chromatography (GPC), high-performance liquid chromatography (HPLC), nuclear magnetic resonance (NMR) or gas/liquid chromatography-mass spectrometry (GC/LC-MS). To clarify liquefaction reactions and the chemical composition of products, many investigators have studied the crystallinity, functional groups and micromorphology of the residue from lignocellulosic liquefaction using XRD (Pan et al, 2007;Ahmadzadeh and Zakaria, 2009), FTIR (Vázquez et al, 1997;Schwanninger et al, 2004;Zou et al, 2009) and SEM (Pan et al, 2007;Ahmadzadeh and Zakaria, 2009;Nasar et al, 2010). As well, the molecular weight and distribution, molecular structures and the amount of free phenol of liquefied products in the presence of phenols or polyhydric alcohols by acid catalysts, were studied using GPC (Deng et al, 2008), GC/LC-MS (Basaran et al, 2003;Zhang et al, 2007;Soria et al, 2008), NMR (Lee and Ohkita, 2004;Lin et al, 2004) and HPLC (Lin et al, 2001a, b;Inoue et al, 2004;Zhang et al, 2005;Zhang et al, 2007).…”
Section: Characterization Of Liquefaction Productsmentioning
confidence: 98%
“…The study of reaction mechanisms must rely on analytical chemical methods, such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), gel permeation chromatography (GPC), high-performance liquid chromatography (HPLC), nuclear magnetic resonance (NMR) or gas/liquid chromatography-mass spectrometry (GC/LC-MS). To clarify liquefaction reactions and the chemical composition of products, many investigators have studied the crystallinity, functional groups and micromorphology of the residue from lignocellulosic liquefaction using XRD (Pan et al, 2007;Ahmadzadeh and Zakaria, 2009), FTIR (Vázquez et al, 1997;Schwanninger et al, 2004;Zou et al, 2009) and SEM (Pan et al, 2007;Ahmadzadeh and Zakaria, 2009;Nasar et al, 2010). As well, the molecular weight and distribution, molecular structures and the amount of free phenol of liquefied products in the presence of phenols or polyhydric alcohols by acid catalysts, were studied using GPC (Deng et al, 2008), GC/LC-MS (Basaran et al, 2003;Zhang et al, 2007;Soria et al, 2008), NMR (Lee and Ohkita, 2004;Lin et al, 2004) and HPLC (Lin et al, 2001a, b;Inoue et al, 2004;Zhang et al, 2005;Zhang et al, 2007).…”
Section: Characterization Of Liquefaction Productsmentioning
confidence: 98%
“…This peak is broad due to the complex vibrational modes arising from a mixture of stretching vibrational bands of -OH groups in hydrogen bonded and chemisorbed water as well as the inter and intramolecular hydrogen bonding vibrations [94,107]. The peak at 2937 cm −1 can be attributed to the symmetric or asymmetric stretching vibrations of the CH 2 and CH 3 groups of side chains and aromatic methoxy groups in the different lignocellulosic structures in the YTBS adsorbent [105,108].…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…These spectra show a broad peak at 3280 cm −1 which is assigned to the (O-H) stretching vibration in hydroxyl groups (commonly appearing between 3550 cm −1 and 3200 cm −1 ) [62]. The groups with this functionality found in the lignocellulosic structure of the YTBS are as follows: absorbed water, aliphatic primary and secondary alcohols found in cellulose, hemicellulose, lignin, extractives, phenols with intermolecular hydrogen bonds, and carboxylic acid groups in the extractives [105,106]. This peak is broad due to the complex vibrational modes arising from a mixture of stretching vibrational bands of -OH groups in hydrogen bonded and chemisorbed water as well as the inter and intramolecular hydrogen bonding vibrations [94,107].…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…However, in recent years there has been an increasing amount of literatures on the potential of liquefied biomass to be used in particular application such as novolak type resins [148], bio-oil [149] and valuable chemicals [150]. Previous studies proved that oil palm biomass wastes, like other lignocellulosic material are suitable to be converted through liquefaction mechanism.…”
Section: Liquefaction Of Oil Palm Biomassmentioning
confidence: 99%
“…Ahmadzadeh and Zakaria [148] carried out a study on the characterization of the liquefied EFB yield in phenol in a reflux condenser system and properties of phenolated EFB resin. They found that high temperature and high catalyst concentrations produced higher liquefaction yields.…”
Section: References Oil Palm Waste(s) Experimental Findingsmentioning
confidence: 99%